Arranging social values for secondary school outcomes and its relationship to their level of ambition - A. Hassan, Reda (International Journal of Psychosocial Rehabilitation, 2020)
Values are from the basic concepts in all fields of educational, economic, political and social life, and that the element of progress and prosperity in human wealth does not grow except through a major tool in education, except values. They are influencing human relations in all their forms because they are a social necessity, and they have standards and goals that must be met in every society. It affects individuals when they form attitudes, motives and aspirations in some social situations and the values express themselves through laws and social organization programs. (Shafiq 1997: 73).And all revolutionary movements in the world seek to create a new mindset and a cultural transformation in society, and since students are part of this society, which assigns responsibilities that lie with them, so it has become necessary to study the values in schools, as we find that many countries of the world have been born in them with tendencies to regulate moral values The prevailing social in their societies, which demonstrates the need to benefit from the experiences of others in this field and the current research seeks to identify the value arrangement of the outputs of secondary schools and thus enhance their choices and goals that they seek by identifying their aspirations and their future aspirations according to a valuable building that calls To honesty, honesty, open mind, and how to behave in different situations and to choose the right choices in their lives.